Pengaruh Profitabilitas dan Likuiditas Terhadap Agresivitas Pajak (Studi pada Perusahaan Energi Subsektor Batu Bara yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Nurmala, Irma; Arafat, Fauzi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the effect of profitability and liquidity on tax aggressiveness in energy companies within the coal subsector listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. Profitability is measured using Return on Assets (ROA), liquidity is measured using the Cash Ratio (CR), and tax aggressiveness is proxied by the Effective Tax Rate (ETR). This is a quantitative study using multiple linear regression analysis. The sample was selected using purposive sampling, resulting in 21 companies from a total population of 35. The data used are secondary data obtained from financial reports published on the official IDX website. The results show that profitability has a significant negative effect on tax aggressiveness, meaning companies with higher profitability tend to be more tax-compliant. Similarly, liquidity has a significant negative effect on tax aggressiveness, indicating that companies with higher liquidity are also more compliant with tax obligations. The partial test (t-test) shows a t-value for profitability of -0.313 (significance 0.017) and for liquidity of -0.068 (significance 0.047). The simultaneous test (F-test) indicates that profitability and liquidity together significantly affect tax aggressiveness, with an F-value of 8.962 and a significance level of 0.000.